Appendectomy may delay Parkinson's disease Onset. Issue 10 (30th July 2015) - Mendes, Alexandre; Gonçalves, Alexandra; Vila‐Chã, Nuno; Moreira, Inês; Fernandes, Joana; Damásio, Joana; Teixeira‐Pinto, Armando; Taipa, Ricardo; Lima, António Bastos; Cavaco, Sara
Abstract Background Alpha‐synuclein (α‐Syn) is particularly abundant in the vermiform appendix, which makes this structure an anatomical candidate for the initiation of Parkinson's disease (PD) pathology. We hypothesized that history of appendectomy might affect PD clinical onset. Methods A total of 295 PD patients enrolled in a comprehensive observational study were asked about past history of appendectomy. Cox's regression, with a time‐dependent covariate, explored the effects of appendectomy on age at PD onset. Results Thirty‐four patients (11.5%) had appendectomy before PD onset. There was no significant effect of appendectomy on age at PD onset for the entire cohort (P = 0.153). However, among patients with late onset (≥55 years), we found evidence that those with past appendectomy had more years of life without PD symptoms than patients without appendectomy (P = 0.040). No association was found for the young‐onset group (P = 0.663). Conclusions An apparent relationship was observed between appendectomy and PD onset in the late PD cohort. © 2015 International Parkinson and Movement Disorder Society